2020
DOI: 10.15421/032012
|View full text |Cite
|
Sign up to set email alerts
|

Variability at winter wheat varieties first generation which obtained mutagen action

Abstract: The purpose of our investigation was to identify the features of the depressive effects of the aftereffect of different doses of gamma-rays on winter wheat varieties of local breeding in terms of germination, survival, morphometry, yield. The parameters of germination and survival, the passage of the main phases of ontogenesis in winter wheat plants of French varieties (Flamenko and Ghayta) at the first generation were studied. The influence of mutagenic depression on parameters of yield structure (morphometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Gorbatova et al (2020) found that the genetic structure of the varieties was an important factor in their response to low doses of gamma rays. Some other research results indicate that the effects of mutagens may vary according to varieties (Nazarenko and Lykholat, 2020;Hong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Gorbatova et al (2020) found that the genetic structure of the varieties was an important factor in their response to low doses of gamma rays. Some other research results indicate that the effects of mutagens may vary according to varieties (Nazarenko and Lykholat, 2020;Hong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Yalin and the line YAA7050-14. F test was used to determine the statistical significance level of the differences, and Duncan's multiple comparison method was used to group the means (Montgomery, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…To achieve sufficient and effective variation in the plant species and cultivars in mutation breeding, it is important to determine the source of the mutagen to be used and the effective dose to be used in advance (Maluszynski et al, 2009) because the effective dose of mutagen depend on the plant species and cultivars (Nazarenko & Lykholat, 2020). In general, the rate of germinated or surviving plants (Ahumada-Flores et al, 2020), the rate of plant developmental retardation (Kodym et al, 2012) and the rate of chlorophyll mutations (Çiftçi & Şenay 2005) are used to determine effective doses and mutation frequencies.…”
Section: Introductionmentioning
confidence: 99%